Identification of natural host range of coconut cadang-cadang viroid and characterization of its small RNAs from oil palm - Mohammadi, Mohammadreza (2014)
Coconut cadang-cadang viroid (CCCVd), a viroid from the genus Cocadviroid in the family Pospiviroidae, is the causal agent of orange spotting disorder in oil palm and variants of CCCVd have been detected and characterized from commercial oil palm plantations in Malaysia. It is considered as a potential threat to oil palm industry while epidemiological aspects of the viroid infection in oil palm are unknown. In order to investigate natural host range of the viroid, 64 leaf samples from 25 plant species from various locations in Selangor state and Kuala Lumpur were collected and tested by Reverse Transcription-Polymerase Chain Reaction (RTPCR) assay. Based on amplification of DNA molecules of ca. 250 bp representing basic monomeric form of the viroid (CCCVd246), CCCVd was detected in 14 plant species including 7 palm, 3 monocotyledonous and 4 dicotyledonous plant species. From the palm species, CCCVd was detected from Cocos nucifera, Corypha utan, Pritchardia pacifica, Ptychosperma macarthurii, Livistona chinensis, Saribus rotundifolius and Wodyetia bifurcata but not from Hyophorbe lagenicaulis, Cyrtostachys renda, Veitchia merrillii, Rhapis excels, Dypsis lutescens and Ravenala madagascariensis. Fourteen out of 16 collected samples from coconut palms (Cocos nucifera) were found to contain CCCVd molecules. From other monocotyledonous and dicotyledonous plant species CCCVd was detected from Heliconia sp., Maranta arundinacea, Etlingera elatior, Pseuderanthemum reticulatum, Codiaeum variegatum, Osmoxylon sp. and Carica papaya but it was not detected from Calathea luthea, Canna sp., Dracaena surculosa and Bauhinia sp. Sequence analysis of 10 isolated CCCVd variants from 9 hosts revealed that there was no sequence variation among the variants. The consensus sequence of the variants was 246 nt in size with 100% homology to oil palm variant (CCCVd-OP246) and exhibiting similar substitutions of C31 by U and G70 by C in P and CCR domains respectively compared to CCCVd246 from coconut palms from the Philippines. Validation of results from RT-PCR was carried out through Two Dimensional- Polyacrylamide Gel Electrophoresis (2D-PAGE) analysis of nucleic acid extract of the samples and by hybridization assay. In 2D-PAGE analysis, bands representing circular viroid RNAs were detected in the samples that were positive for CCCVd in RT-PCR and not in CCCVd negative samples. In hybridization assay these bands were hybridized with high stringency to full length digoxigenin (DIG) labeled cRNA probe and colorimetric signal was produced in their positions on membrane. In order to investigate the occurrence of Post-Transcriptional Gene Silencing (PTGS) and CCCVd small RNAs accumulation in oil palm, total small RNAs of 20-30 nt from two CCCVd infected asymptomatic and symptomatic oil palms were isolated and cloned. Small RNAs of full homology to CCCVd sequence were not detected among the sequenced clones. An attempt was made to establish Next Generation Sequencing (NGS) for detection of CCCVd variants from oil palm. Analysis of data obtained from deep sequencing of RNAs from a CCCVd infected oil palm showed that populations of CCCVd variants or other novel viroids were not detected but a 365 nt plant rRNA sequence was detected that was erroneously deposited in GenBank as Yucatan isolates of Citrus exocortis viroid (CEVd).